Chinese expert consensus on minimally invasive radical surgery for pancreatic ductal adenocarcinoma (version 2022). Issue 3 (29th August 2022) - Zhao, Yupei; Yu, Xianjun; Wang, Wei; Mou, Yiping; Jiang, Chongyi; ,
Abstract : Various types of minimally invasive pancreatic surgery have been carried out in the last decades with promising outcomes reported by early explorers. Nevertheless, there are still controversies on oncologic outcomes and safety in the use of minimally invasive radical surgery for pancreatic ductal adenocarcinoma (PDAC). This consensus, referring to Chinese expert opinions and worldwide researches, aimed to discuss the related issues on minimally invasive radical surgery for PDAC to ensure the perioperative and oncological outcomes. Quality of evidence and strength of recommendations were evaluated based on the GRADE approach. The 15 recommendations covered 5 topics: oncological outcomes and patient safety of laparoscopic and robotic pancreatoduodenectomy, left-side pancreatectomy for PDAC, learning curve, safety of neoadjuvant therapy, and vascular resection in minimally invasive radical surgery for PDAC. This consensus gives reference and guidance to surgeons on the use of minimally invasive radical surgery for PDAC. Although this consensus is not sufficient to answer all the questions about minimally invasive radical surgery for PDAC, it represents the current consensus on the application of the techniques in the treatment of PDAC on the Chinese mainland.